Mucinous cholangiocarcinoma: Clinicopathological features of the rarest type of cholangiocarcinoma. Issue 2 (7th June 2017) - Sumiyoshi, Tatsuaki; Shima, Yasuo; Okabayashi, Takehiro; Ishikawa, Ayako; Matsumoto, Manabu; Iwata, Jun; Morita, Sojiro; Sueda, Taijiro
Abstract: Mucinous cholangiocarcinoma is extremely rare and its clinicopathological features remain unclear. The present study aimed to analyze published data on mucinous cholangiocarcinoma. Medical databases were searched from 1980 to 2016, and clinicopathological data for 16 mucinous cholangiocarcinoma patients were obtained. Characteristic imaging findings, including hypovascular tumor with peripheral enhancement on computed tomography and angiography, extremely high intensity on T2‐weighted magnetic resonance images, intratumoral calcification and luminal communication between the tumor and bile duct on cholangiography, were noted. Mucinous cholangiocarcinoma was correctly diagnosed in one patient only, with some patients diagnosed as low‐malignant biliary cystic tumors preoperatively. Five cases were followed up after the first medical examination, and three of these were initially diagnosed as biliary cystadenoma or intraductal papillary neoplasm of the bile duct. All five tumors showed marked enlargement within 4 months of follow up. Macroscopically, the resected tumors were non‐cystic/solid in seven cases, and cystic in seven. Tumor diameter ranged from 5 cm to 22 cm, and mucoid cut surface, lobulation, lack of capsule and papillary growth were observed. Microscopically, co‐existing intraductal papillary neoplasm of the bile duct was noted in three of five patients with available data. Nine of 10 cases in whom the pathological stage was reported had advanced disease with lymph node and/or distant metastasis, and 5‐year survival was achieved in one microinvasive case only. Overall 1‐ and 3‐year survival rates were 60.1% and 40.1%, respectively. The possibility of mucinous cholangiocarcinoma should be considered when biliary cystic tumors are detected on imaging modalities, despite the rarity of this tumor. Abstract : Mucinous cholangiocarcinoma is extremely. However, mucinous cholangiocarcinoma may show marked rapid growth, and therefore, the possibility of this tumor should be considered when biliary cystic tumors are detected on imaging modalities.